Progranulin Is Associated with Disease Activity in Patients with Rheumatoid Arthritis - Cerezo, Lucie Andrés; Kuklová, Markéta; Hulejová, Hana; Vernerová, Zdeňka; Kaspříková, Nikola; Veigl, David; Pavelka, Karel; Vencovský, Jiří; Šenolt, Ladislav (Mediators of inflammation, 2015)
OBJECTIVE: Progranulin (PGRN) is implicated in the pathogenesis of rheumatoid arthritis (RA). The aim of this study was to assess the relationship between PGRN and disease activity in RA. METHODS: PGRN levels were evaluated in patients with RA (n = 47) and OA (n = 42) and healthy controls (n = 41). Immunohistochemical analysis of PGRN in synovial tissues was performed. The association between PGRN and C-reactive protein (CRP), disease activity score (DAS28-CRP), and health assessment questionnaire (HAQ) was studied. RESULTS: Circulating PGRN was elevated in patients with RA and OA compared to healthy controls (227.1 ± 100.2 and 221.5 ± 102.5 versus 128.1 ± 34.7 ng/mL; P < 0.001). Synovial fluid levels of PGRN were higher in patients with RA compared to OA (384.5 ± 275.3 versus 241.4 ± 165.2 ng/mL; P = 0.002). PGRN expression was significantly upregulated in the synovial tissue of RA patients particularly in the inflammatory infiltrates. Serum PGRN levels correlated with DAS28 (r = 0.327, P = 0.049) and HAQ score (r = 0.323, P = 0.032), while synovial fluid PGRN correlated only with HAQ (r = 0.310, P = 0.043) in patients with RA. PGRN levels were not associated with CRP or autoantibodies. CONCLUSIONS: This study demonstrates increased PGRN expression at local sites of inflammation and association between PGRN levels, disease activity, and functional impairment in patients with RA.
Keywords: mezibuněčné signální peptidy a proteiny; Arthritis, Rheumatoid; Female; revmatoidní artritida; C-Reactive Protein; Intercellular Signaling Peptides and Proteins; ženské pohlaví; lidé; synoviální tekutina; Synovial Membrane; synoviální membrána; Male; Aged; Progranulins; progranuliny; Synovial Fluid; lidé středního věku; C-reaktivní protein; senioři; mužské pohlaví; Middle Aged; Humans